Fusion of an Fc chain to a VHH boosts the accumulation levels in Arabidopsis seeds. Issue 8 (6th August 2013) - De Buck, Sylvie; Nolf, Jonah; De Meyer, Thomas; Virdi, Vikram; De Wilde, Kirsten; Van Lerberge, Els; Van Droogenbroeck, Bart; Depicker, Ann
Summary: Nanobodies ® (VHHs) provide powerful tools in therapeutic and biotechnological applications. Nevertheless, for some applications, bivalent antibodies perform much better, and for this, an Fc chain can be fused to the VHH domain, resulting in a bivalent homodimeric VHH‐Fc complex. However, the production of bivalent antibodies in Escherichia coli is rather inefficient. Therefore, we compared the production of VHH7 and VHH7‐Fc as antibodies of interest in Arabidopsis seeds for detecting prostate‐specific antigen (PSA), a well‐known biomarker for prostate cancer in the early stages of tumour development. The influence of the signal sequence (camel versus plant) and that of the Fc chain origin (human, mouse or pig) were evaluated. The accumulation levels of VHHs were very low, with a maximum of 0.13% VHH of total soluble protein (TSP) in homozygous T3 seeds, while VHH‐Fc accumulation levels were at least 10‐ to 100‐fold higher, with a maximum of 16.25% VHH‐Fc of TSP. Both the camel and plant signal peptides were efficiently cleaved off and did not affect the accumulation levels. However, the Fc chain origin strongly affected the degree of proteolysis, but only had a slight influence on the accumulation level. Analysis of the mRNA levels suggested that the low amount of VHHs produced in Arabidopsis seeds was not due to a failure in transcription, but rather to translation inefficiency, protein instability and/or degradation. Most importantly, the plant‐produced VHH7 and VHH7‐Fc antibodies were functional in detecting PSA and could thus be used for diagnostic applications.